2022
DOI: 10.5501/wjv.v11.i2.111
|View full text |Cite
|
Sign up to set email alerts
|

Novel appearance of hyperglycemia/diabetes, associated with COVID-19

Abstract: In a recent meta-analysis the prevalence of coronavirus disease 2019 (COVID-19)-associated hyperglycemia was 25%, and that of COVID-19-associated new-onset diabetes was 19%. An association between hyperglycemia or new-onset diabetes and COVID-19 has been suggested. In a recent relevant study of critically and non-critically ill patients with COVID-19, we found that indeed beta-cell function was compromised in critically ill patients with COVID-19 and that these patients showed a high glycemic gap. Nevertheless… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…One-quarter of critically ill patients without prior history of diabetes have stress hyperglycemia [ 8 ]; the latter is attributed to activation of the HPA axis, increased insulin resistance, and release of proinflammatory cytokines [ 9 ].…”
Section: Non-covid-19 Critical Illnessmentioning
confidence: 99%
See 1 more Smart Citation
“…One-quarter of critically ill patients without prior history of diabetes have stress hyperglycemia [ 8 ]; the latter is attributed to activation of the HPA axis, increased insulin resistance, and release of proinflammatory cytokines [ 9 ].…”
Section: Non-covid-19 Critical Illnessmentioning
confidence: 99%
“…Yet, fairly recently, we observed that in ICU-hospitalized patients with COVID-19 and no history of diabetes, beta cell function was overtly negatively affected [ 52 ]. Stress hyperglycemia in COVID-19 patients in the ICU may obscure the incidence of COVID-19-attributable hyperglycemia/new-onset diabetes [ 8 ]. Up to the time of drafting this work, the international registry of COVID-19-related diabetes established in 2020 (COVIDIAB; , accessed on 25 August 2022) has not put forth any of its data [ 53 ]; it would be most interesting to see due to its international scale.…”
Section: Endocrine Aspects Of Sars-cov-2 Infectionmentioning
confidence: 99%